(untitled) (Research, Society and Development, 2021)
The corn and soybean intercropping can increase the quality of the silage and result in higher animal productivity. This research aimed to evaluate the agronomic aspects of intercropped corn + soybean, fermentative and bromatological profile of the intercropping silage, in function of the plant spatial arrangement, and types of fertilization. Two tests were performed; test 1: being in simple arrangement (a corn line alternated with a soybean line); test (2) in double arrangement (two corn lines alternated with a soybean line). The experimental design was a randomized block design in a 2x2 + 1 factorial scheme, with four replications. The first factor was constituted of two sowing fertilization modalities in the line: only in corn, and in total area; the second factor, were the seeding fertilization types: 100 and 70 kg ha-1 P2O5 and K2O, respectively (Dose 1) and 150 and 95 kg ha-1 of P2O5 and K2O, respectively (Dose 2). The additional treatment corresponded to corn monoculture. After harvesting, the material was ensiled for 60 days. There was no statistical difference in the yield of silage between treatments, only increases in the production of soybean pods and in the quality of the silage in the higher doses of fertilization. The results show that the soybean addition in corn silage causes greater losses during the fermentation process, but in contrast increases the protein and ether extract contents and digestibility. Pointing out that a roughage with these characteristics may supply protein supplementation in ruminant diets.